SISTEM PAKAR IDENTIFIKASI TINGKAT STRES AKADEMIK SISWA KELAS XII SMK MENGGUNAKAN METODE CERTAINTY FACTOR - Rivan Dwi Ferdiansyah (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Academic stress arises when academic demands are perceived to exceed a student's ability to cope. At SMK Bina Industri, identifying grade XII students' academic stress level is still done manually through observation and counseling by Guidance and Counseling (BK) teachers, making it time-consuming and subjective. This study designs and builds a web-based expert system to identify students' academic stress levels quickly, systematically, and objectively using the Certainty Factor (CF) method. The system was developed with the Prototype model through communication, quick plan, modeling quick design, construction of prototype, and deployment delivery and feedback stages. The knowledge base was obtained through observation, interviews with BK teachers and a psychology expert, and literature study, resulting in 22 symptoms grouped into three stress-level categories: low, moderate, and high. The system design is illustrated through a use case diagram and an activity diagram. Testing results show that all system functions worked as required, with a user-acceptance index ranging from 87.16% to 89.40%, categorized as very good, so the system can help BK teachers conduct initial identification and monitoring of students' academic stress more effectively.